Typology of the Reality Status Category in Selected Languages. Is the Habitual in Polish an Instance of (Ir)realis or Modality? - Pietras, Paulina (Respectus Philologicus, 2017)
The present article is aimed at examining the category of the reality status by discussing the dichotomy “realis / irrealis” in the context of the categories of modality, habituality and futurity. Prototype analysis is juxtaposed with scope analysis, and the category of the habitual is discussed from the typological perspective as well as from the perspective of its connection with the category of futurity. The paper presents aspect diversity of habituals (perfective and imperfective aspect and its contextual implications) as well as the differentiation between the habitual and modality. A special focus is on the prototype analysis and its application instances in Polish, English and Hebrew. The primary objective of the paper is to show that, although it is possible to treat irrealis as notional category, the habituals in Polish and many other Slavic languages (e.g. Czech) should be identified with the modality domain rather than irrealis category. The paper is also an attempt to provide an insight into the distinction between (ir)realis and encoding systems of modalities as the habitual aspect displays modal category features in many languages (including Polish).